The Effect of Udder Measurements on Somatic Cell Count and Daily Milk Production in Holstein Cattle - Ayhan Ceyhan; Mahmut Çınar; Ugur Serbester (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out to investigate the effect of udder measurements group on somatic cell count (SCC) and daily milk production. Milk samples and udder measurements were collected monthly from 79 lactating Holstein cows on commercial dairy in the province of Niğde. In the study, front teat length (FTL), rear teat length (RTL), front teat diameter (FTD), rear teat diameter (RTD), distance between front teats (DBFT), distance between rear teats (DBRT), front udder height, (FTH), rear udder height (RUH), distance between front and rear teats (DBST) were obtained in before afternoon milking. Udder measurements were divided into 5 groups according to the measurements. The effect of DBFT, DBRT, FTH, RTD, FTD and DBRT groups on daily milk production were statistically significant, while FTH, RUH and DBRT were found non-significant. The effect of udder measurements groups on SCC was found not significant, except rear teat diameter (RTD). Average daily milk production and SCC were estimated as 28.25 kg/day and 274.90 cell/ml, respectively. In conclusion, it can be said that the distance between teats, teat’s diameter and front udder height of Holstein cattle is important factor for milk yield of Holstein dairy cattle. Also, SCC is effected by rear teat diameter.